POLITIK EKONOMI ZISWAF SEBAGAI KONTRAK SOSIAL JAMINAN KESEJAHTERAAN - Zuhrinal M Nawawi (Studia Economica : Jurnal Ekonomi Islam, 2015)
In the Indonesian context, the political economy of Islam embodied in the form of government intervention, such as making the rules, get into the industry, initiating a movement, and others. Zakat, as a form of moral responsibility that is both ethical fardlu 'ain for every Muslim. If realized productively, it will be able to empower the social economy. Zakat is not merely consumptive consumable donations, but they can be used in the form of community development programs. Potential sources of Islamic philanthropy is Infak, Sadaqah and Waqf. It would be nice, if it is enabled philanthropy funds in the form of community empowerment through a million entrepreneurs, for example. More useful, and does not degrade Indonesia in the eyes of other nations. ZISWAF as a source of Islamic philanthropy should be utilized to achieve the welfare of the people. Government support in the form of political economy based on the principles of Islamic economics make progress and economic growth in the practice of Islam in Indonesia became rapidly.